Methyl cinnamate protects against dextran sulfate sodium-induced colitis in mice by inhibiting the MAPK signaling pathway - E Lilin; Li Wenjie; Hu Yuanjia; Deng Lijuan; Yao Jianping; Zhou Xingwang (Acta Biochimica et Biophysica Sinica, 2023)
Effective and non-toxic therapeutic agents are lacking for the prevention and treatment of colitis. Previous studies found that methyl cinnamate (MC), extracted from galangal ( Alpinia officinarum Hance), has anti-inflammatory properties. However, whether MC is effective as anti-colitis therapy remains unknown. In this study, we investigate the therapeutic effects of MC on dextran sulfate sodium (DSS)-induced colitis in mice and further explore its potential mechanism of action. MC treatment relieves symptoms associated with DSS-induced colitis, including the recovery of DSS-induced weight loss, decreases the disease activity index score, and increases the colon length without toxic side effects. MC treatment protects the integrity of the intestinal barrier in mice with DSS-induced colitis and inhibits the overexpression of pro-inflammatory cytokines in vivo and in vitro. Moreover, the MAPK signaling pathway is found to be closely related to the treatment with MC of colitis. Western blot analysis show that phosphorylation of the p38 protein in colon tissues treated with MC is markedly reduced and phosphorylation levels of the p38, JNK and ERK proteins are significantly decreased in RAW 264.7 cells treated with MC, indicating that the mechanism of MC in treating DSS-induced colitis could be achieved by inhibiting the MAPK signaling pathway. Furthermore, 16S RNA sequencing analysis show that MC can improve intestinal microbial dysbiosis in mice with DSS-induced colitis. Altogether, these findings suggest that MC may be a novel therapeutic candidate with anti-colitis efficacy. Furthermore, MC treatment relieves the symptoms of colitis by inhibiting the MAPK signaling pathway and improving the intestinal microbiota.